Frenula Treatment Recommendations for Pedodontic Patients According to the Guidelines (International Journal of Food and Nutritional Sciences, 2022)
There are three distinct types of frenula, also known as folds of the mucous membrane that can be seen in the oral cavity. The primary purpose of these frenula is to support the lips and the tongue. Children might be affected by a wide variety of developmental issues due to abnormalities in their labial and lingual frenula. In recent years, there has been a rise in the number of people being diagnosed with this condition, as well as an increase in the number of surgical procedures performed to repair their attachment. The purpose of this research is to give diagnostic and therapeutic criteria, as well as conduct a literature review on the current guidelines of therapy for frenula in pedodontic patients. A review of the most recent research on diseases of the oral frenulum was carried out, and a search of the PubMed/MEDLINE database covering the last five years was carried out. In addition, a discussion of the most recent recommendations made by the American Association of Pediatric Dentistry was incorporated into the study (AAPD). Clinicians may find use in the most recent set of guidelines that have been proposed by the American Academy of Pediatric Dentistry. It is recommended, however, that additional research be conducted in order to discover whether or whether there is a causal association between difficulty in nursing, pronunciation problems, and improper frenal attachment.